On the fixed points of an affine transformation: an elementary view - Kovács, Zoltán (Teaching Mathematics and Computer Science, 2006)
This note shows how the fixed points of an affine transformation in the plane can be constructed by an elementary geometric method. The approach presented here also shows how the affinities of the plane can be classified with the help of their fixed points.